P118 Extending conceptualisations of care-seeking behaviour: qualitative findings from follow-up interviews with participants from the third National Survey of Sexual Attitudes and Lifestyles (Natsal-3). (13th September 2016) - Mapp, F
Abstract : Background: Existing definitions of care-seeking behaviour do not sufficiently capture individual lived experience and decision-making processes. I explore underlying mechanisms of care-seeking in response to symptoms and propose a new explanatory model. Methods: I identified a sampling frame of 639 participants who participated in the third National Survey of Sexual Attitudes and Lifestyles and reported at least one genito-urinary symptom, no previous attendance at sexual health clinics and had consented to be re-contacted. Purposive sampling was used to select a sample with maximum diversity of symptomatic experience. Participants were contacted by letter and followed-up by telephone to arrange the interview at their home. I carried out semi-structured interviews focussing on sexually transmitted infections (STI) perceptions, symptom meanings, care-seeking behaviour and stigma between May 2014 and March 2015 which were digitally recorded and transcribed verbatim. I used Interpretative Phenomenological Analysis to explore lived experiences of symptoms and decision-making about healthcare needs. NVivo facilitated data organisation and coding and one third of transcripts were double-coded. This work is part of a mixed Methods study with greater qualitative weighting exploring how perceptions of STIs influence symptom experiences and care-seeking behaviours. Results: I interviewed 16 women and 11 men aged 19–47 years living in Britain. Accounts of pain urinating and abnormal vaginal discharge in women and pain urinating and painful testicles in men were most common. Fourteen participants described seeking care for genito-urinary symptoms at their GP, four reported visiting a sexual health clinic and seven had not sought any care. Care-seeking behaviour was selective and dependent on making sense of sensations via an iterative and interpretive process of determining levels of concern about bodily changes and forming perceptions about possible causes. Concern was influenced by severity, familiarity, duration and perceived impact on future health and suspected causes were viewed as medical issues, lifestyle factors or random occurrences. Sense-making processes were disrupted by attending healthcare if the cause was perceived as medical. From our findings we developed an extended model of care-seeking based on theories of behaviour change. It incorporates processes that occur between feeling sensations to outcomes of care-seeking behaviour including non-attendance. Conclusion: Care-seeking in response to symptoms is mediated by concern and perceived causes; decision-making processes extend beyond symptom recognition and service choice. Data is limited by recall bias. My model builds on existing care-seeking and behaviour change theories to extend conceptualisations of care-seeking processes and may improve pathways into healthcare.